Association of Maternal Vitamin B12 Status With Infant Findings and Neurodevelopment in Vitamin B12-Deficient Breast-fed Babies. Issue 1 (January 2022) - Keskin, Ebru Yilmaz; Keskin, Mahmut; Karaibrahimoğlu, Adnan
Abstract : Few studies have examined the association between maternal vitamin B12 status and their breast-fed infants' findings. The objective of this study was to analyze the association of maternal B12 status with infant findings including neurodevelopmental outcome in breast-fed babies with B12 deficiency. Correlation analyses between the laboratory findings of infants with B12 deficiency ( n =120) and their mothers were performed and the association of maternal B12 status with infant findings including the Denver-II developmental screening test (DDST II) results was examined. There was a significant correlation between infant and maternal B12 levels ( r =0.222; P =0.030), and between infant and maternal homocysteine (Hcy) levels ( r =0.390; P <0.001). Among the babies 4 months of age or older, maternal Hcy levels were significantly correlated with infant mean corpuscular hemoglobin ( r =0.404; P =0.001) and infant mean corpuscular volume ( r =0.461; P <0.001). Mothers of infants with abnormal DDST II had lower vitamin B12 (196.9±41.2 vs. 247.0±77.0 pg/mL; P =0.018) and higher Hcy levels (17.3±5.0 vs. 10.7±3.1 µmol/L; P <0.001) than mothers of infants with normal DDST II. A lower maternal vitamin B12 status may be related to impaired neurodevelopment in breast-fed infants with vitamin B12 deficiency. Pregnant and lactating women should be offered easy access to healthy nutrition and vitamin B12 supplements.